Cancer nanotechnology: Enhancing tumor cell response to chemotherapy for hepatocellular carcinoma therapy - Yongbing Sun; Wen Ma; Yuanyuan Yang; Mengxue He; Aimin Li; Lei Bai; Bin Yu; Zhiqiang Yu (Elsevier, 2019)
Hepatocellular carcinoma (HCC) is one of the deadliest cancers due to its complexities, reoccurrence after surgical resection, metastasis and heterogeneity. In addition to sorafenib and lenvatinib for the treatment of HCC approved by FDA, various strategies including transarterial chemoembolization, radiotherapy, locoregional therapy and chemotherapy have been investigated in clinics. Recently, cancer nanotechnology has got great attention for the treatment of various cancers including HCC. Both passive and active targetings are progressing at a steady rate. Herein, we describe the lessons learned from pathogenesis of HCC and the understanding of targeted and non-targeted nanoparticles used for the delivery of small molecules, monoclonal antibodies, miRNAs and peptides. Exploring current efficacy is to enhance tumor cell response of chemotherapy. It highlights the opportunities and challenges faced by nanotechnologies in contemporary hepatocellular carcinoma therapy, where personalized medicine is increasingly becoming the mainstay. Overall objective of this review is to enhance our understanding in the design and development of nanotechnology for treatment of HCC. Keywords: Hepatocellular carcinoma, Cancer nanotechnology, Cell response, Chemotherapy